Evaluation of Delaware Stars for Early Success Year 1 Report - Schwartz, Heather L. (RAND Corporation, 2014)
As a first step in a larger study of Delaware Stars, a voluntary quality rating and improvement system (QRIS) for early learning and care programs, RAND researchers examined prior QRIS validation research, analyzed Delaware Stars administrative data, conducted key stakeholder interviews and focus groups, and implemented a virtual pilot test using national data to identify relationships between program quality and child developmental outcomes.